Multidisciplinary residential home intervention to improve outcomes for frail residents - Anna Steel; Helen Hopwood; Elizabeth Goodwin; Elizabeth L. Sampson (BMC, 2022)
Abstract Background Residential homes provide accommodation and assistance with personal care only and are not required to have registered nurses on site. However, their residents often have a combination of comorbidity, polypharmacy, frailty and mental-health conditions with poor access to healthcare to meet these needs. Integrated healthcare for older people is a key NHS priority in the Long-Term Plan and the Five-Year Forward View. We describe development and implementation of multi-disciplinary intervention to integrate healthcare and promote interprofessional education. Methods A multi-disciplinary residential home quality improvement project in two cycles by a team comprising senior and trainee general practitioners, trainees in geriatrics, psychiatry, pharmacist and residential home senior staff. The intervention was underpinned by the framework for enhanced health in care homes including Comprehensive Geriatric Assessment (CGA) and mental-health review. Each intervention session included an educational presentation by a team member consideration of each resident in a pre-evaluation multi-disciplinary discussion followed by a structured clinical assessment and discussion of proposed management. Results Three residential homes participated with a total 34 residents receiving intervention. In one residential home, there was a 75% reduction in admissions for those reviewed and a reduction in overall admission costs. Polypharmacy was reduced by an average of 2 medications per resident across the three sites. There was a 63% increase in cardio-pulmonary resuscitation decisions and 76% increase in advance care planning discussions. Conclusion This was an effective model for multi-disciplinary trainees working with a perceived impact on physical and mental health, and valuable opportunities for sharing learning.